Potentials of Carbon Stored in Plant Biomass at Little Farmers Grassland Cisarua, West Bandung Regency - Annas Dwitri Malik; Komang Yoga Zso Zsa Dewa; Parikesit Parikesit; Susanti Withaningsih; Ratna Wingit (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Alternatives of vegetations to store carbon need to be encouraged considering that forests are threatened by widespread destructions. One such vegetation is grasslands which have the potential for carbon storage and to reduce CO2 concentration in the atmosphere. At present, many enterprises have designed grasslands for animal feed. Grassland at Little Farmers, Cisarua, West Bandung was established for many purposes, i.e. recreation, education, and animal feed. The purpose of this research was to study the potential of carbon stock in grassland vegetation at this location. Based on RaCSA method, the tree biomass was determined by nondestructive collection of density and basal area of trees, then calculated by an allometric equation. The ground cover biomass was determined by destructive collection of grass and roots. Total measured biomass was multiplied by 46% to obtain carbon storage. Based on the results, the potential of carbon stock in Little Farmers grassland is 6,506.23 kg/m2 with the potential for carbon storage below the ground (0.129 kg / m2) was slightly higher than the carbon stored above the ground Â (0.101 kg / m2). Carbon stored in ground cover had been proven to be lower than woody plants (6,506 kg / m2). This study has pioneered in finding the carbon stocks potential of a man-made grassland, so it provides basis of an alternative land use that can be encouraged for carbon sequestration. For many enterprises, this study will aid in the conduct and management planning of grasslands with regards to ecosystem services preservation, such as carbon sequestration.